2008
DOI: 10.1373/clinchem.2007.102046
|View full text |Cite
|
Sign up to set email alerts
|

Association between the UGT1A1 TA-Repeat Polymorphism and Bilirubin Concentration in Patients with Intermittent Claudication: Results from the CAVASIC Study

Abstract: Background: Bilirubin has antioxidative and cytoprotective properties. Low plasma concentrations of bilirubin are reportedly associated with the development of coronary and cerebrovascular disease, and bilirubin concentrations are strongly correlated with the enzyme activity of the hepatic uridine diphosphate glucuronosyltransferase (UGT1A1). The activity of UGT1A1 is influenced by a TA-repeat polymorphism in the promoter of the UGT1A1 gene (UDP glucuronosyltransferase 1 family, polypeptide A1). In a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 30 publications
3
46
2
1
Order By: Relevance
“…The largest of these studies analysed 7,075 individuals from the National Health and Nutrition Examination Survey, and reported that increased bilirubin levels were associated with a reduced prevalence of PAD [19]. However, hard clinical endpoints were not explored in that and other similar smaller case-control studies [17][18][19][20]. Our study therefore for the first time extends these findings to amputation events.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The largest of these studies analysed 7,075 individuals from the National Health and Nutrition Examination Survey, and reported that increased bilirubin levels were associated with a reduced prevalence of PAD [19]. However, hard clinical endpoints were not explored in that and other similar smaller case-control studies [17][18][19][20]. Our study therefore for the first time extends these findings to amputation events.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with this notion, case-control studies have reported that individuals with elevated bilirubin levels caused by Gilbert's syndrome have a decreased incidence of atherosclerotic disease compared with normal controls [12,14]. Also, previous studies reported an inverse relationship between bilirubin levels and PAD prevalence [17][18][19][20]. However, the association between bilirubin and the hard clinical endpoint of amputation events has not been reported, to our knowledge.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The CAVASIC (CArdioVAScular disease in Intermittent Claudication) Study is a case-control study with a prospective follow-up investigation of patients to identify cardiovascular risk factors in male patients with intermittent claudication [8][9][10] Inclusion criterion for patients (n = 256) was a history of intermittent claudication (PAD IIa or IIb according to the criteria of Fontaine) irrespective of any former treatment procedure (bypass surgery or intervention). Patients who presented with acute or critical limb ischemia (Fontaine III or IV), impaired kidney function with serum creatinine > 1.5 mg/dL, malignancy, previous organ transplantation, and therapy with nicotinic acid or corticosteroids were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%